2020
DOI: 10.1016/j.radonc.2020.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial-to-mesenchymal transition is a prognostic marker for patient outcome in advanced stage HNSCC patients treated with chemoradiotherapy

Abstract: Background: The prognosis of patients with HPV-negative advanced stage head and neck squamous cell carcinoma (HNSCC) remains poor. No prognostic markers other than TNM staging are routinely used in clinic. Epithelial-to-mesenchymal transition (EMT) has been shown to be a strong prognostic factor in other cancer types. The purpose of this study was to determine the role of EMT in HPV-negative HNSCC outcomes. Methods: Pretreatment tumor material from patients of two cohorts, totalling 174 cisplatin-based chemora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 44 publications
1
11
0
Order By: Relevance
“…The high failure rate among Slug-positive patients treated with primary RT/CRT is likely due to the high number of tumor cells in EMT, which is a characteristic associated with radio-and chemotherapy resistance [24,46] and tumor stemness [21]. In previous invitro studies, we observed Slug to be expressed in HNC cell lines, where EMT was induced by co-cultivation with fibroblasts [47].…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The high failure rate among Slug-positive patients treated with primary RT/CRT is likely due to the high number of tumor cells in EMT, which is a characteristic associated with radio-and chemotherapy resistance [24,46] and tumor stemness [21]. In previous invitro studies, we observed Slug to be expressed in HNC cell lines, where EMT was induced by co-cultivation with fibroblasts [47].…”
Section: Discussionmentioning
confidence: 80%
“…In vitro, the induction of EMT in HNSCC cell lines doubled cisplatin resistance and increased radioresistance with a dose-modifying factor of 2 compared with the unmodified cell line [22,23]. EMT-related gene signatures are associated with radio-and chemotherapy resistance in patients with HNSCC [24]. We recently reported that EMT can be quantified in tumor samples from HNSCC patients using multichannel fluorescence image cytometry by evaluating the coexpression of epithelial and mesenchymal proteins in tumor cells [25].…”
Section: Introductionmentioning
confidence: 99%
“…We tested the conformity of the four clinical hypoxia profiles in 224 HNSCC patients. To this end, we combined gene expression data generated from three HNSCC cohorts (Table 1): Pramana (published), de Jong 1 (expanded expression data set with additional samples that could not be used in the original study) and unpublished gene expression data from a patient cohort as described in de Jong 2 et al [32,33,34,35,36]. Patient characteristics of the cohorts are available in Supplementary Materials, Tables S3–S5.…”
Section: Resultsmentioning
confidence: 99%
“…So, to test whether the prognostic value of acute hypoxia is independent of HPV, we aimed to validate the prognostic relevance of acute hypoxia in a HPV-negative HNSCC cohort. To this end, we collected clinical and gene expression data from a study by Van der Heijden et al [35,36]. This data derived from pre-treatment patient tumor material of two cohorts of HPV-negative advanced stage HNSCC patients, NKI-CRAD and DESIGN, comprising 174 patients in total.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation